Estudo preliminar da presença de vírus em populações de capivaras em dois biomas brasileiros - Lara Ambrosio Leal Dutra (2015)
Capybaras (Hydrochoerus hydrochaeris) are the largest known living rodents, being endemic of the New World and living in a diversity of habitats, as long as it is close to water bodies. Two mains characteristics exhibited by this animal support its great potential of playing a role in diseases transmission at border zones between wild and domestic habitat: easy adaptation to modified habitats, showing preference to nearby farm areas, and they have a tendency to population growth in these environment, due to favorable conditions presented in these areas. These changes in population dynamics represents a change in ecological relationship between species that support the traffic of known and unknown infectious agents through capybaras movements between environments. So, capybaras may be closely related to diseases emergence in wild and domestic populations. Its presence in these border areas is increasing recently promoted by the intense process in which man activities grows driving environments changes and, despite the potential risk presented, little is known about viruses in capybaras. The studies held on so far had presented only poor evidences of relationship and focused on viruses of domestic animals due to its economic value. The goal of this study was to start a preliminary investigation about the presence of various viral groups in capybaras using a non invasive approach. This research was performed by using capybaras fecal samples in qPCR tests and viral isolation. The qPCR tests searched for molecular evidences of the presence of virus in several capybaras population on two Brazilian biomes, Cerrado and Pantanal. The results pointed to the putative presence of several viruses targeted among several samples. Search for more molecular evidence of Orthopoxvirus (OPV) presence was held in three suspicious samples and several target genes were tested by qPCR and PCR. The results pointed to the presence of viral DNA in both three samples. This work also yielded isolation of two viruses that still must be characterized. So this work describes for the first time the presence of molecular evidence of OPV in capybaras, presenting strong evidence that this animal plays a role in the natural transmission chain of Vaccinia virus in Brazil. Besides that, this research presents suspicion on the presence of several viral groups in capybaras concerning human and animal health that must be target for future investigations in order to understand the role of capybaras on viral circulation dynamics. And finally, this work allows a guidance of viruss investigation in its relationship with capybaras by pointing the better population to conduct further investigations.